2020
DOI: 10.1111/jppi.12329
|View full text |Cite
|
Sign up to set email alerts
|

Establishing and Maintaining Couple Relationships as Perceived by Couples with Intellectual Disabilities: Implications for Families, Support Staff, and Policy Change

Abstract: Couple relationships are central to adult lives in the general population, but less accessible to adults with intellectual disabilities (ID). However, little is known regarding factors that enable couple relationships among this population. In the present study, semistructured interviews were conducted with 20 Israeli couples with ID. The interview protocol addressed conditions that enabled the relationship, challenges encountered in the relationship, and coping strategies employed in accordance. Thematic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…They also show the compensatory role of love in the face of unpleasant interpersonal relationships experienced in the past (Bates et al, 2016). The sexual experiences, desires, needs and thought of people with ID presented in the studies have a lot in common with behaviors typical of non-disabled people (Black & Kammes, 2019;Neuman, 2020). This confirms the assumption that positive experiences in relationships, such as love, intimacy and others, are the source of people with ID life normalization.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…They also show the compensatory role of love in the face of unpleasant interpersonal relationships experienced in the past (Bates et al, 2016). The sexual experiences, desires, needs and thought of people with ID presented in the studies have a lot in common with behaviors typical of non-disabled people (Black & Kammes, 2019;Neuman, 2020). This confirms the assumption that positive experiences in relationships, such as love, intimacy and others, are the source of people with ID life normalization.…”
Section: Discussionsupporting
confidence: 69%
“…The analyzed perspective included the previous, current and planned experiences of the respondents. Only a few analyses were carried out with the participation of both partners (Lafferty et al, 2013;Neuman, 2020). The following general and specific aspects were identified: 1) Establishing relationships: preferences and choosing a partner, phases of creating a relationship (Bates et al, 2017;Neuman, 2020).…”
Section: Problem Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…One of the challenges parents face when their child with intellectual disabilities reach adulthood relates to their interest in interpersonal relationships in general and in couple relationships in particular (Neuman, 2017). Most research with regard to parents' perceptions of couple relationships involving their adult children with intellectual disabilities focuses on the sexual aspect of close and intimate relationships and their fears of unwanted pregnancy or sexual abuse (Cuskelly, Bryde, & Centre, 2004;Evans, McGuire, Healy, & Carley, 2009;Garbutt, Boycott-Garnett, Tattersall, & Dunn, 2010;Haynes, 2016;Hollomotz, Speak, & up Committee, 2008;Pownall et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also found parents expressing fear and doubt about their children's ability to form relationships, make reasonable choices regarding romantic partners, manage sexual desires and make appropriate decisions about family planning (Haynes, 2016;Pownall et al, 2012). These negative perceptions may help explain the finding that adults with intellectual disabilities seldom regard their parents as a source of support in creating and maintaining couple relationships (Neuman, 2017).…”
Section: Introductionmentioning
confidence: 99%